Matsumoto Jiichirō and the making of democracy in postwar Japan - Neary, I (Routledge, 2007)
Matsumoto Jiichirō (1887-1966) is best known for his role as leader of the Buraku anti-discrimination movement in Japan. He was chairman and main sponsor of the pre-war Suiheisha and re-assumed a leading role when the movement re-emerged in the late 1940s, creating the Buraku Liberation League in 1955. In addition to this, he was a successful businessman whose construction company, the Matsumoto-gumi, built bridges and public buildings across Fukuoka. His reputation as a role model within the Buraku community cannot be overestimated. However, I do not intend to focus on these aspects of this life in this article. Rather I want to look at his contribution to the wider debate about democratizing postwar Japan.